Faktor yang Mempengaruhi Opini Going Concern (Studi pada Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia) - Hantono Hantono (Politeknik Negeri Lampung, 2019)
This study aims to examine and analyze the influence of leverage, earnings management, and company growth to audit going concern opinion on the basic and chemical industries listed on the Stock Exchange for the period 2012-2016. As an explanatory research, this research used descriptive quantitative approach. The study population was 65 financial statements of basic industrial and chemical companies, with a purposive sampling technique. The research samples were 22 basic and chemical industry financial statements for the period of 2012-2016. The method of data analysis in this study is logistic regression analysis. The results of this study indicate that simultaneously leverage, earnings management, and company growth have a significant effect on the going concern audit opinion on the Basic and Chemical Industries listed on the IDX for the period 2012-2016. Partially leverage, earnings management, and company growth have no effect on going concern audit on Basic and Chemical Industries listed on the Stock Exchange for the period 2012-2016 with a significant value> 0.05. The results of Nagelkerke's R Square value in this study are 0.042 which can state that the dependent variable variability (going concern audit) can be explained by the variability of independent variables (leverage, earnings management and company growth) 42% while the remainder equals 58% explained by independent variables others. Keywords: Leverage, Earnings Management, Growth of Company, Audit, Going Concern Opinion